Fatigue assessment of additively-manufactured C-18150 copper alloy at room and elevated temperatures via a microstructure-sensitive algorithm. (June 2022) - Jirandehi, Arash P.; Khonsari, M.M.; Guo, S.; Gradl, Paul
Highlights: Fatigue damage accumulation in additively manufactured C-18150 is studied for elevated temperatures. The efficacy of microstructure-sensitive fatigue damage/life algorithm is investigated. FEM is used to obtain the specimen's surface temperature evolution. Material's FFE remains within a narrow band at environmental temperatures up to 426 °C. Abstract: The efficacy of a recently developed microstructure-sensitive fatigue framework is assessed for additively manufactured materials at different environmental temperatures. C-18150 copper alloy samples additively manufactured using the Laser Powder Bed Fusion process (L-PBF) are fatigue tested at the room, 204 °C, and 426 °C temperatures. Plastic strain energy as the damage representative is studied via the cyclic stress–strain hysteresis loop area measurements and analyzed via a microstructure-sensitive algorithm. A thermodynamics-based framework is used to calculate Fracture Fatigue Entropy (FFE) to assess the material's fatigue performance. The results based on the hysteresis loop and the microstructure-sensitive method agree both in trend and magnitude.